PENGEMBANGAN BAHAN AJAR MATERI SISTEM KEKEBALAN TUBUH MANUSIA BERBASIS PENGETAHUAN AWAL SISWA SMA - Lutfia Nur Hadiyanti; Ari Widodo (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: Human immunity system concept is close to student’s daily life. So that, there is a big opportunity to students to get prior knowlegde from their own or other person’s experience and other sources. Every science teacher should know students’ prior knowledge to plan approriate teaching materials and methods. This research is conducted to develop a student’s prior knowledge-based of human immune system concept learning material. The study is a research and development with model of educational reconstruction. Sample used is 33 senior high school students from Pemalang and Bandung which is taken by convenience sampling. Results show that the highest understanding are in 1st, 8th, and 9th proposition. The highest misconception is in 2nd proposition. Some propositions are revised based on judgement. Teaching material draft is arranged based on students prior knowledge and prepositions judgment. Keywords: human immunity system, prior knowledge, learning material